2005
DOI: 10.2460/javma.2005.226.1102
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, echocardiographic, and electrocardiographic abnormalities in Boxers with cardiomyopathy and left ventricular systolic dysfunction: 48 cases (1985–2003)

Abstract: Results suggest that Boxers with cardiomyopathy and left ventricular dysfunction frequently have arrhythmias of supraventricular or ventricular origin. Whether ventricular dysfunction was preceded by electrical disturbances could not be determined from these data, and the natural history of myocardial disease in Boxers requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 9 publications
5
38
1
1
Order By: Relevance
“…Although the age of the animal at diagnosis has been statistically significant at univariate Cox analysis, it didn't show any significance in the multivariate analysis, characterizing age only as a risk factor and not as a prognostic factor. In fact, Boxer ARVC is a disease of adult onset that results in worsening of the degree of ventricular arrhythmia that is proportional with the age of affected animals (Moïse, 1999, Baumwart et al, 2005. Thus, older animals are expected to exhibit a greater tendency for sudden death due to the higher number or severity of ventricular arrhythmias or CHF secondary to ventricular dilation and systolic dysfunction .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the age of the animal at diagnosis has been statistically significant at univariate Cox analysis, it didn't show any significance in the multivariate analysis, characterizing age only as a risk factor and not as a prognostic factor. In fact, Boxer ARVC is a disease of adult onset that results in worsening of the degree of ventricular arrhythmia that is proportional with the age of affected animals (Moïse, 1999, Baumwart et al, 2005. Thus, older animals are expected to exhibit a greater tendency for sudden death due to the higher number or severity of ventricular arrhythmias or CHF secondary to ventricular dilation and systolic dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a dog may present subclinical disease or present with syncope or sudden death as a result of ventricular arrhythmias. More rarely, these dogs may present with signs of congestive heart failure due to systolic dysfunction and biventricular dilation that mimic idiopathic dilated cardiomyopathy; supraventricular tachyarrhythmias, such as atrial fibrillation, are also possible in these dogs (Harpster, 1983;Bright and McEntee, 1995;Moïse, 1999;Sisson et al, 1999;Corrado et al 2000;Meurs, 2004;Basso et al, 2004;Baumwart et al, 2005). Although most reports affirm that this type of Boxer ARVC is diagnosed less frequently, a European study found a higher incidence of this form of the disease .…”
Section: Introductionmentioning
confidence: 99%
“…In a prior study of 188 Boxers assessed by 24‐hour ambulatory ECG (AECG), more than 30% of the dogs had more than 100 ventricular premature depolarizations in 24 hours, which has been proposed as a criterion for the diagnosis of ARVC 4 . Although some Boxers also develop overt myocardial failure and dilated cardiomyopathy, the relationship between ARVC and the presence or development of left ventricular (LV) dysfunction is unclear 7,8 …”
mentioning
confidence: 99%
“…Idiopathic ventricular arrhythmia or arrhythmogenic right ventricular cardiomyopathy with right bundle-branch block appearing VT was the working diagnosis. 1 Medical therapy was changed from mexiletine to sotalol, c 1.2 mg/kg PO q12h. The dog presented similarly on several occasions (day 20, day 24, day 45).…”
mentioning
confidence: 99%